Hebe de Bonafini, president of the Mothers of the Plaza de Mayo, adressing a crowd in the Plaza de Mayo - Rypka, Don,
Hebe de Bonafini, president of the Mothers of the Plaza de Mayo, adressing a crowd in the Plaza de Mayo.